Caracterización morfológica de poblaciones nativas de chirimoya (Annona Cherimola Mill.) con fines de aprovechamiento en la provincia de Loja. - Yaguana Uday, Fernanda Patricia (2018)
The chirimoya is originally from the south of Ecuador, specifically from the province of Loja. It is widely consumed worldwide, but in its country of origin, it is still an undervalued fruit tree, despite its exceptional nutritional characteristics. In Ecuador, there is little information on the variability of chirimoya, which would allow us to boost this native genetic material with a view to implementing cash crops. The research work entitled "Morphological characterization of native populations of cherimoya (Annona cherimola Mill.) for use in the province of Loja" had the objective of identifying the variability of this fruit tree in forest fragments of the cantons of Calvas, Espíndola, Loja and Paltas, province of Loja; using the morphological descriptor of chirimoya for trees, leaves, fruits, seeds and flowers from Biodiversity International and CHERLA, a database was developed and multivariate cluster analysis (dendogram) for quantitative descriptors and multivariate correspondence analysis for qualitative descriptors was used, using the fruit-seed database and based on quality standards regulations for fruit marketing to more than one consumption preference survey, the second objective, selected fruit from potentially commercial trees, was met. The results obtained with respect to the variability of the species, gave the obtaining of 4 conglomerates (morphotypes) of which morphotype 2 presented better morphological characteristics. In the correspondence analysis, a fully defined morphotype was identified; in the exocarp type, forms not described by the Chirimoya chirimoya characterizer were identified, so the description of double print was added to 15 entries and the description of another type of exocarp was added to 5 individual entries. Regarding the selection of morphotypes with commercial aptitudes, 9 trees C014, C016, C024, C029, C034, S011, T023, T033, T033, T037 were selected that can be used in future improvement works of the species.